Influence of polycyclic aromatic hydrocarbon and genetic polymorphisms (cyp1a1, gstm1, gstt1) on pyrene metabolite and dna damage among children in the Klang Valley, Malaysia - Hisamuddin, Nur Hazirah (2022)
Polycyclic Aromatic Hydrocarbon (PAHs) are hazardous particulate matter boundorganic compound found in urban atmospheric environment. Exposure to PAHs is of great concern to public health especially for children, due to their ubiquitous presence in the environment and well-recognised carcinogenicity, teratogenicity and genotoxicity to human health. This study aimed to assess the association of particulate PAHs exposure on biomarker of PAHs exposure, urinary 1-hydroxypyrene (1-OHP) and DNA damage among children in the vicinity of heavy traffic areas in the Klang Valley. In addition, this study investigated the effects of genetic polymorphisms of PAHs metabolising enzymes on the concentrations of pyrene metabolite, the urinary 1-OHP level, and on DNA damage in children. This cross-sectional comparative study was conducted at eight primary schools in high traffic (HT) and low traffic (LT) areas in Klang Valley, Malaysia. A validated questionnaire on socio-demographic, health status, personal exposure and dietary intake was distributed to randomly selected children. The indoor and outdoor samples of particulate matter PM2.5-bound PAHs were collected using a MiniVol portable air sampler for 24 h. PAHs concentration was quantified using Gas Chromatography-Mass Spectrometry (GC-MS). Source diagnostic ratio was applied to determine the source of PAHs emission. DNA damage in buccal cells were evaluated using Comet Assay, while urinary 1-OHP was assessed using High-Performance Liquid Chromatography (HPLC). Genes encoding three PAHs-metabolising enzymes CYP1A1, GSTT1 and GSTM1 were studied for polymorphisms using PCR-RFLP and multiplex PCR. The results showed that the total outdoor PAHs was higher (range between 1.36- 5.76 ng/m3) than indoor environments (range between 1.25-5.58 ng/m3). The concentration of total PAHs was higher at HT compared to LT area. Based on the source diagnostic ratio, PAHs in the HT area is pyrogenic, mainly from high combustion activity (vehicular emission). Meanwhile, the urinary 1-OHP concentration was significantly higher among children in HT as compared to LT (0.07 vs 0.04 μmol/mol-creatinine). The DNA damage was obviously higher among children in HT as compared to LT. A significant association were found between environmental PAHs exposure with urinary 1-OHP and DNA damage. It was observed that there was no significant effect of CYP1A1, GSTM1 and GSTT1 genotypes on urinary 1-OHP and DNA damage levels. The 95th percentile of the incremental lifetime cancer risk (ILCR) using Monte Carlo simulation showed that the inhalation risk for the children in HT and LT area were 2.80 × 10-7 and 1.43 × 10-7, respectively. After controlling the possible confounders, the result from multiple linear regression showed that PAHs exposure was the most significant factor associated with urinary 1-OHP and DNA damage among children. This study provided evidence that children living near heavy traffic area are more likely to be exposed to environmental PAHs and have a higher risk of DNA damage than children living in low traffic areas. Findings from this study will be able to help in minimising the potential health effect related to traffic related air pollution in urban area by designing a mitigation plan for school.